PARASITIC DISEASES IN CHILDREN - Abdullayev U. M.; Azzamova Sh. U.; Abdumalikova M. D. (Web of Journals Publishing, 2025)
Parasitic infections in children remain a major concern in global public health. This analytical article examines the prevalence, risk factors, and socio-hygienic contexts of intestinal parasites and other parasitic diseases affecting children. Recent studies (for example, in Egypt, where the prevalence among preschool and school-aged children was found to be approximately 46.5%) demonstrate that poor sanitation and economic disadvantages are strongly associated with increased infection risk. This article analyzes the epidemiological status of parasitic diseases in children and outlines prevention strategies.
Keywords: Children; parasitic infection; intestinal helminths; hygiene factors; epidemiology; prevention.